UPAYA GURU DALAM MENANGANI KARAKTER SISWA YANG HETEROGEN SEBAGAI DAMPAK SISTEM ZONASI DI SMPN 5 GRESIK - Devinta Nur Amalia; Muhammad Turhan Yani (Kajian Moral dan Kewarganegaraan, 2021)
This study aims to describe the character of students received from the zoning system and to find out the teacher's efforts in dealing with the heterogeneous character of students as the impact of the zoning system at UPT SMPN 5 Gresik and to provide an understanding for the teacher to appropriate the efforts used to deal with the heterogeneous character of students as a impact of the zoning system. The theory used is the theory of good character foarmation by Thomas Lickona. The concept of this theory shows that character is formed into three interrelated parts, namely moral knowledge, moral feelings, and moral behavior. The research method used is a qualitative approach with an exploratory design. Data collection techniques using observation, in-depth interviews, and documentation. The selection of informants as the source of the research data was selected by using purposive sampling technique. The informants of this study include Pancasila & Citizenship Education Teachers, Counseling Guidance Teachers, Islamic Religious Education Teachers and Deputy Principals for Student Affairs. The results of the research carried out revealed that the character of the zoning system students was considered poor brcause they do not have enough tolerance, discipline, responsible, and the efforts made by the teacher, namely by implementing 5S habits in learning at school so that students were more polite towards teachers and peers. The teacher gives punishment to students with poor character. The teacher will conduct individual counseling and provide group guidance and provide reinforcement through religious activities. Keywords: Teachers, Character, Zoning